Estimation of effectivenes of spine biomechanical correction Kozyavkin method (INRS) in children with spastic form of Cerebral Palsy - V I Kozyavkin; O V Kozyavkina; N V Kozyavkina; М S Gordiyevych; V I Lysovych; Т B Voloshyn; W Zukow; I L Popovych (Kazimierz Wielki University, 2015)
Kozyavkin V I, Kozyavkina O V, Kozyavkina N V, Gordiyevych М S, Lysovych V I, Voloshyn Т B, Zukow W, Popovych I L. Estimation of effectivenes of spine biomechanical correction Kozyavkin method (INRS) in children with spastic form of Cerebral Palsy. Journal of Education, Health and Sport. 2015;5(2):208-217. ISSN 2391-8306. DOI: 10.5281/zenodo.16046 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%282%29%3A208-217 https://pbn.nauka.gov.pl/works/545791 http://dx.doi.org/10.5281/zenodo.16046 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.10.2014. Revised 18.01.2015. Accepted: 25.02.2015.     ESTIMATION OF EFFECTIVENES OF SPINE BIOMECHANICAL CORRECTION KOZYAVKIN METHOD (INRS) IN CHILDREN WITH SPASTIC FORM OF CEREBRAL PALSY   VI KOZYAVKIN1, OV KOZYAVKINA1, NV KOZYAVKINA1, МS GORDIYEVYCH1, VI LYSOVYCH1, ТB VOLOSHYN1, W ŻUKOW2, IL POPOVYCH3,1   1International Clinic of Rehabilitation, Truskavets', Ukraine center@reha.lviv.ua 2Faculty of Physical Education, Health and Tourism, Kazimierz Wielki University, Bydgoszcz, Poland w.zukow@ukw.edu.pl 3OO Bohomolets' Institute of Physioilogy National Academy of Sciences, Kyiv, Ukraine i.popovych@biph.kiev.ua   Abstract It is presented results of clinical-physiological observations in 108 children (girls and boys equally) aged 4÷17 years with spastic forms of cerebral palsy. State of Gross Motor Function was 1÷4 levels at GMFCS, the functional state of the hand was 1÷3 levels at MACS. Firstly carried out for both handes Dynamometry, Box and Block Test and Nine Hole Peg Test before and after one spine biomechanical correction Kozyavkin method (INRS) (in 54 children) or its imitation (in 54 children). Then children of first group received two-week course of rehabilitation by INRS while children of second (control) group received usual treatment. In children of control group were detected small but significance changes in Box and Block Test: increase by 12,0±1,7% right and by 9,1±1,7% left, while changes in Nine Hole Peg Test as well as in Dynamometry were insignificance (by +4,1±2,2% and -5,8±6,0% right and by +3,9±2,6% and -2,3±4,8% left correspondingly). Therefore then these children received course of rehabilitation by INRS also and analyse of results conducted for united group (108 children). It is detected increase in Box and Block Test by 22,9±2,2% right and by 19,1±1,3% left, in Nine Hole Peg Test by 16,7±1,9% right and by 18,8±1,8% left, in Dynamometry by 30,6±5,0% right and by 31,6±6,1% left. In total effectivenes of spine biomechanical correction Kozyavkin method makes average 23,3±1,6% versus 3,5±1,4% in control. Keywords: Cerebral palsy, Dynamometry, Box and Block Test, Nine Hole Peg Test, Intensive Neurophysiological Rehabilitation by Kozyavkin method (INRS), effectivenes.